“Robotics and Zoom:” Using Online Focus Groups to Explore Future-Food Technologies - Errmann, Amy; Conroy, Denise (SAGE Publishing, 2023)
Increases in the global population mean there are pressures on the food supply. To address this, future-food technologies (FFTs) are being considered to increase food production. However, consumers may differ in their adoption of FFTs according to individual beliefs, attitudes, and perceptions. One case that explored this issue has been completed by The New Zealand Institute for Plant and Food Research Limited, within the “Horticulture Production Goes Urban (HgU)” research program. We explored the topic through market research that utilized online focus groups (OFGs). OFGs are an important qualitative method to consider as a researcher and they will become more predominant given the disruptions from the COVID-19 pandemic on research. We provide a pragmatic approach to the OFG method, using FFTs as a topic exemplar. Key learning outcomes include how to conduct, apply, and navigate research decisions using OFGs to gather primary data of high quality.
Keywords: 1302 Curriculum and Pedagogy; 1608 Sociology; 1699 Other Studies in Human Society; 44 Human society; 47 Language, communication and culture; agriculture; moderator; recruitment; robotics; attitudes